MAC protocol design for WLAN to enhance IEEE 802.11 - Go, Cheng Yee. (2013)
According to Gast (2002), the highest throughput that can be attained by using the DCF is 75% of the nominal bit rate. This project proposes enhancement solutions which aims to achieve at least a 20% increment of the total channel throughput.